Elizabeth Taylor : the grit & glamour of an icon - Brower, Kate Andersen (Harper, an imprint of HarperCollinsPublishers, 2022)
"No celebrity rivals Elizabeth Taylor's glamour and guts or her level of fame. She was the last major star to come out of the old Hollywood studio system and she is a legend known for her beauty and her magnetic screen presence in a career that spanned most of the twentieth century and nearly sixty films. But her private life was even more compelling than her Oscar-winning on-screen performances. During her seventy-nine years of rapid-fire love and loss she was married eight times to seven different men. Above all, she was a survivor--by the time she was twenty-six she was twice divorced and once widowed. Her life was a soap opera that ended in a deeply meaningful way when she became the first major celebrity activist to lead the fight against HIV/AIDS. A co-founder of amfAR, she raised more than $100 million for research and patient care. She was also a shrewd businesswoman who made a fortune as the first celebrity perfumer who always demanded to be paid what she was worth. In the first ever authorized biography of the Hollywood icon, Kate Andersen Brower reveals the world through Elizabeth's eyes. Brower uses Elizabeth's unpublished letters, diary entries, and off-the-record interview transcripts as well as interviews with 250 of her closest friends and family to tell the full, unvarnished story of her remarkable career and her explosive private life that made headlines worldwide. Elizabeth Taylor captures this intelligent, empathetic, tenacious, volatile, and complex woman as never before, from her rise to massive fame at age twelve in National Velvet to becoming the first to negotiate a million-dollar salary for a film, from her eight marriages and enduring love affair with Richard Burton to her lifelong battle with addiction and her courageous efforts as an AIDS activist. Here is a fascinating and complete portrait worthy of the legendary star and her legacy."--Amazon.com.